ANALISIS HASIL JANGKA PENDEK PELAKSANAAN KONSELING PEMBERIAN MAKAN BAYI DAN ANAK MENGGUNAKAN PEMODELAN RASCH (GIZI INDONESIA, 2018)
The first thousand days of life is a golden period that determines the quality of life in the future. Practice of Infant and Young Child Feeding (IYCF) that are not appropriate during this period can cause stunting. One of the government’s efforts to improve IYCF practice is IYCF Counseling. IYCF counseling can improve knowledge, attitude, and encourage the occurance of IYCF behavior. This study aims to analyze the short results of IYCF counseling on the knowledge and attitude of Mothers who have and have not been given IYCF counseling in Cireunghas District, Sukabumi. The instrument was used a modified knowledge and attitude questionnaire about IYCF. Rasch modeling was used for analysis of questionnaire data, the design of this study was a survey method with a cross sectional approach in April 2018 with maternal subjects having children aged 6-23 months totaling 90 people. The items on the instrument are found to have varying discrimination, which indicates that the instrument has the ability to measure. The results show that the counseling material that needs to be emphasized during IYCF counseling is about giving breastfeeding using bottles, giving up to 2 yearsof breastfeeding, the texture of food at the beginning of complementary feeding, and responsive feeding. There needs to be increase in the quality and frequency of IYCF counseling to achieve the expected changes of knowledge and attitude.